כאב החיבור עם הכאב: ארבעה פרקים על שירת חדוה הרכבי - הירשפלד אריאל (מכאן, 2016)
This first part of this essay deals with the relations between Hedva Harechavi’s poetry and Lea Goldberg, her tutor and mentor during Harechavi’s formative years as a poetess. The second part analyses the stylistic difference between Harechavi’s poetry and that of Ravikovitch and Wallach. The third part of the essay deals with meter, rhythm and repetition in her poetry and the final part addresses polyphony in her poetry.